IMPLEMENTASI STOCK OPNAME DALAM MENINGKATKAN PENGENDALIAN INTERN PADA KOPERASI KARYAWAN (Studi Kasus Koperasi Karyawan PT. Platinum Ceramics Industry Lebaniwaras, Kec. Wringinanom, Kab. Gresik) - Muthi Dwika Ningrum; Miya Dewi Suprihandari (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
In order to maintain the quality of the cooperative, the warehousing system must also be maintained so that the stored goods are controlled both physically and systemically, so that this makes it easier for employees to run the wheels of work optimally and efficiently. One of the things that can be done to control the stock of goods is stock-opname. This research is motivated because stock-opname activities can maintain the quality of inventory and maximise development activities in employee cooperatives. The purpose of this study was to determine (1) How to implement stock-taking in improving internal control in the PCI Employee Cooperative. (2) How is the implementation of internal control systems and procedures over the inventory of trade goods applied to the PCI Employee Cooperative. This research uses a qualitative approach; information is collected through interviews, observations, and documentation before being subjected to descriptive analysis. Primary and secondary data are used as data sources in this study. The results showed that the PCI Employee Cooperative in conducting stock-opname was able to implement in accordance with the principles of internal control, which included separation of duties, authorisation and documentation, physical and asset control, independent examination, reporting and feedback. PCI Employee Cooperative also shows that it has implemented adequate internal control systems and procedures over trade goods inventory, seen from several aspects such as a conducive control environment, appropriate risk assessment, effective control activities, periodic stock-taking, detailed and accurate recording systems, and clear receiving, storing and issuing procedures.